Tri‐Layer Laminated Fabric‐Induced Sweating Surfaces for Passive Cooling. Issue 3 (1st February 2021) - Li, Xiaoyan; Javed, Muhammad; Luo, Ming; Cai, Zaisheng; Xu, Bi
Abstract: Fabrics which can keep people cool in a hot climate have attracted considerable attention in recent years. Among various cooling strategies, fabric cooling by water evaporation is proved to be very safe, simple and sustainable. Here, a tri‐layer laminated fabric (TLF) inspired by perspiration is designed to realize passive cooling of human body. An interlayer fabric which is coated with crosslinked sodium polyacrylate can absorb and store a large amount of water. A moisture‐absorbing and quick‐drying fabric is used as the outer layer while a waterproof breathable fabric is used on the inside of the laminate in contact with skin. The prepared TLF shows decent evaporative cooling performance under dry heat conditions. The water absorbency of TLF is about 400% higher than that of pristine cotton after 1 h soaking in water. Under a 1 sun irradiation (1000 W m −2 ), the indoor temperature of a simulated room can be reduced by ≈5–7 °C compared with the other without a cooling system. Meanwhile, the evaporative cooling effect can be maintained up to 5 h. This cooling fabric shows broad application prospects in the fields of thermal cooling to human and buildings. Abstract : A tri‐layer laminated fabric (TLF) inspired by perspiration is designed to realize passive cooling. The prepared TLF can absorb and store a large amount of water. The water evaporates slowly, leading to decent cooling performance under dry heat conditions. This fabric uses external environment to drive water for evaporative cooling, achieving zero energy consumption during the entire cooling process.